A multi gene-approach genotyping method identifies 24 genetic clusters within the genotype II-European African swine fever viruses circulating from 2007 to 2022 - Gallardo, Carmina; Casado, Nadia; Soler, Alejandro; Djadjovski, Igor; Krivko, Laura; Madueño, Encarnación; Nieto, Raquel; Perez, Covadonga; Simon, Alicia; Ivanova, Emiliya; Donescu, Daniel; Milicevik, Vesna; et al. (Frontiers in Veterinary Science, 2023)
African swine fever (ASF) is a contagious viral disease of pigs and wild boar that poses a major threat to the global swine industry. The genotype II African swine fever virus (ASFV) entered the European Union (EU) in 2014 and since then fourteen countries have been affected, Italy and North Macedonia being the last in 2022. To further our understanding of the epidemiology and spread of ASFV, 382 isolates from Europe were sequenced by analyzing six genetic markers. The combination of the results obtained by sequencing these variable regions allowed to differentiate the European II-ASFV genotypes into 24 different groups. In addition, the SNP identified in the IGR I329L-I215L region, not previously described, grouped the viruses from North Macedonia that caused the 2022 outbreaks with viruses from Romania, Bulgaria, Serbia and Greece, differentiating from other genotype II isolates present in Europe and Asia. Furthermore, tandem repeat sequence (TRS) within the 9R-10R genes of the multigene family 505 (MGF505) revealed eight different variants circulating. These findings describe a new multi-gene approach sequencing method that can be used in routine genotyping to determine the origin of new introductions in ASF-free areas and track infection dynamics in endemic areas.